Comparison of Bioabsorbable Magnesium versus Titanium Screw Fixation for Modified Distal Chevron Osteotomy in Hallux Valgus. (19th November 2018) - Acar, Baver; Kose, Ozkan; Turan, Adil; Unal, Melih; Kati, Yusuf Alper; Guler, Ferhat
Abstract : Objective . The purpose of this retrospective study was to compare the clinical and radiological results of magnesium versus titanium screw fixation for modified distal chevron osteotomy in hallux valgus (HV). Materials and Methods. A total of 31 patients who underwent modified distal chevron osteotomy for HV deformity between 2014 and 2017 were reviewed retrospectively. Headless magnesium (Mg) compression screw fixation was applied in 16 patients (17 feet) and headless titanium (Ti) compression screw in 15 patients (17 feet). Patients were followed up for at least 12 months with a mean of 19.0 ± 6.8 months in the Mg screw group and 16.2 ± 6.19 in the Ti screw group, respectively (p: 0.234). Clinical results were evaluated using the American Orthopedic Foot and Ankle Society Hallux metatarsophalangeal-interphalangeal (AOFAS-MTP-IP) scale and a visual analogue scale (VAS). The hallux valgus angle (HVA) and intermetatarsal angle (IMA) were measured before and after surgery. Time to osteotomy union and any complications were recorded and compared between the groups. Results . An improvement in the AOFAS-MTP-IP scale and VAS points were recorded in both groups with no statistically significant difference between the groups (p: 0.764 and 0.535, resp.). At the final follow-up examination, HVA and IMA were similar (p: 0.226 and 0.712, resp.). There was no significant loss of correction between the early and final radiographs in respect of HVA and IMA in both groups (p: 0.321 and p: 0.067). Full union of the osteotomy was obtained in all patients. Prolonged (1.5 months) swelling and mild hyperemia around the surgical incision were observed in 1 patient in the Mg group but there was a good response to physical and medical therapy, and the complaints were completely resolved. There were no other significant complications in either group. Conclusion . The results of this study showed that bioabsorbable Mg compression screw fixation has similar therapeutic efficacy to Ti screw fixation in respect of functional and radiological outcomes. Bioabsorbable Mg screw is an alternative fixation material that can be safely used for modified distal chevron osteotomy in HV surgery.